Pengaruh Penundaan Sentrifugasi dan Penyimpanan Darah pada Kadar Kolesterol Total - M. Ibnu Ubaidillah; Hery Prambudi; Oktafirani Al As; Rizal Ibrahim Aji (Jurnal Sains dan Kesehatan, 2021)
Laboratory examination is very important to diagnose a disease, one of which is the examination of total cholesterol to diagnose heart disease, this examination uses serum samples obtained from blood clots that have been centrifuged, various variations of freezing are carried out to accelerate the examination results ranging from blood that is immediately centrifuged and blood that is allowed to freeze for 5-10 minutes, while according to PERMENKES No. 43 of 2013 to get blood serum allowed to freeze for 20-30 minutes at room temperature which is then centrifuged. This study aims to determine the results of differences in total cholesterol levels in blood samples immediately centrifuged and blood samples that are allowed to freeze at room temperature 260C for 10 and 20 minutes before centrifugation. The method used in this study is an experimental research method, this examination uses the CHOD-PAP enzymatic colorimetric method. For data analysis using the SPSS program using the one way anova test. This study was conducted on 15 respondents obtained from students of An Nasher Health Analyst Academy Cirebon randomly. The results of the examination of total cholesterol levels in blood samples that were immediately centrifuged had an average value of 205.8 mg/dl with the lowest value of 112 mg/dl and the highest value of 314 mg/dl, while in blood samples that were allowed to freeze for 10 minutes had an average value of 188 mg/dl with the lowest value of 144 mg/dl and the highest value of 278 mg/dl, and in blood samples that were allowed to freeze for 20 minutes had an average value of 142.6 mg/dl with the lowest value of 95 mg/dl and the highest value of 186 mg/dl. The results of this study indicate that there is a significant difference in total cholesterol levels in blood samples immediately centrifuged and blood samples left to freeze at room temperature 260C for 10 and 20 minutes before centrifugation.